Monetary Policy and Stock Market Return: The Case of Saudi Arabia Interest Rates hikes and Stocks Returns - Alalmai, Somaiyah Fahad; AlGhanmi, Alyaa Talal (Journal of Economic, Administrative and Legal Sciences, 2024)
The purpose of this research is to examine whether changes in macroeconomic variables have an effect on Saudi Arabia’s main index, TASI and whether Monetary policy actions produce positive, negative or no effect at all for all listed companies. Accordingly, we examine the stock price adjustment around announcements of changes in interest rates, we examine the impact of a series of interest rate hikes on the stock returns under the main stock index in the Saudi Stock Market, TASI. The data covers four events between 16 March 2021 to 5 October 2022. We use an event study approach, with an estimation window length of [-250,-11] and an event window length of [-10,7], and we apply the OLS market model for daily data. The significance of the cumulative abnormal return CAAR is tested using the t statistics. The empirical results show that TASI responds negatively to three out of four announcements of interest rate hikes. The positive reaction occurs during the July 2022 monetary action. The positive reaction is attributed to the rising oil prices during that period. Finally, the results of this research open a window for future research to examine the impact of interest rates on the Saudi stock market over the long run.